Direct hydrodynamic measurements at the upper shoreface of a sandy beach in Paraná - Brazil - Mauricio A. Noernberg; Pedro A. Rodrido (Ocean and Coastal Research)
Sandy shorelines show heightened susceptibility to alterations, highlighting the importance of reliable field measurements in forecasting coastal evolution. This study offers direct hydrodynamic measurements from the upper shoreface of a sandy beach in Paraná. We observed five distinct oceanographic conditions, including a high-energy event. Notably, wave height showed a positive correlation with northward longshore currents. During pre- and post-frontal periods, cross-shore flow predominates over longshore currents, particularly evident during low tides with pronounced offshore flow. These findings provide valuable insights for researchers seeking to quantify and model longshore sediment transport dynamics and morphological changes along sandy coastlines.